On stable C-symmetries for a class of PT-symmetric operators - Patsyuck, O. M. (Methods of Functional Analysis and Topology, 2013)
Recently, much attention is paid to the consideration of physical models described by PT-symmetric Hamiltonians. In this paper, we establish a necessary and sufficient condition for existence of a stable C-symmetry for a class of PT-symmetric extensions of a symmetric operator S with deficiency indices (2,2).